2020
DOI: 10.22305/ict-unpa.v12.n4.752
|View full text |Cite
|
Sign up to set email alerts
|

El uso de sistemas de información geográfica en la identificación y valoración de recursos geoturísticos

Abstract: Los Sistemas de Información Geográfica son herramientas fundamentales para el análisis espacial en general y para las investigaciones turísticas en particular, ya que permiten plasmar una problemática e interpretar los resultados desde otra perspectiva. En este marco, este trabajo se propone georreferenciar, mapear y valorar recursos de la geodiversidad en el Valle del Río Pipo y el Cañadón de la Oveja (54°49'52"S - 68°24'51"W), próximos a la ciudad de Ushuaia en Tierra del Fuego (Argentina). Para ello se desa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Flores (2020) proposed different geotourist products to enhance the urban tourist offer in southern Tierra del Fuego. Cohen et al (2020) have identified and mapped georesources of different morphogenetic origins in a glacial valley in Cañadón de la Oveja. In this sense, Tierra del Fuego should be considered as a faraway destination capable of fulfilling tourists' expectations as regards interesting and attractive georesources.…”
Section: Geodiversity Resources As Geotourist Attractionsmentioning
confidence: 99%
“…Flores (2020) proposed different geotourist products to enhance the urban tourist offer in southern Tierra del Fuego. Cohen et al (2020) have identified and mapped georesources of different morphogenetic origins in a glacial valley in Cañadón de la Oveja. In this sense, Tierra del Fuego should be considered as a faraway destination capable of fulfilling tourists' expectations as regards interesting and attractive georesources.…”
Section: Geodiversity Resources As Geotourist Attractionsmentioning
confidence: 99%